Qualitative - Binary, Nominal and Ordinal Data Analysis in Medical Science - Swati Patel (Medsci Publications, 2022)
The outcome of any medical research is belonged to the human beings. The correct application of statistical test has its paramount importance. This article provides the details of categorical data analysis test with example and with its interpretation. It is included when to use Chi-square test (2*2 & R*C), Yate`s Correction, Fisher Exact test, Mc Nemartest manually as well as using Open Epi and R codes.